Professional baking - Gisslen, Wayne 1946- (John Wiley & Sons, 2013)
"Gisslen's 6th edition of Professional Baking continues to educate hundreds of thousands of readers with clear, detailed instructions in the theory and techniques necessary to meet the demands of the professional kitchen. The text continues to comprehensively cover baking basics while also offering enhanced coverage of higher-level techniques such as pastry, chocolate, and sugar work. Balancing theory and practice, Professional Baking provides both the understanding and performance abilities needed to progress and develop in a successful baking career" -- Provided by publisher.